Mobilitas Pekerja, Remitan dan Peluang Berusaha di Pedesaan - Effendi, Tadjudin Nur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2004)
The impact of labor mobility on rural development has received considerable attention from scholars and planner. On the one hand, some scholars and urban planners believe that labor mobility has negative effects on rural development partly it result in a cause lack of human resources to support regional development activities. In addition, they believe that rural-urban migration has created problems, such as unemployment, the spread of informal activities, poverty, and other social problems. On the other hand, they argue that labor mobility has positive effects on rural development. Labor mobility has been seen as a household survival strategy in response to the socio-economic change resulting from inequality of the market expansion. By involving in the urban labor market, especially in informal activities, migrants are able to share the fruits of development which tend to be concentrated in particular regions (urban areas). Some scholars believe that remittances sent by migrants to their places of origin may stimulate the growth of business activities in these areas. By examining some empirical studies, this article discusses the impact of labor mobility on business opportunities in areas of out-migration.